Purchase Decisions From Social Media Marketing, Product Innovation, and Celebrity Endorser - Safira Ardian Sagita; Sarsono Sarsono (Almana : Jurnal Manajemen dan Bisnis, 2021)
Investing or saving with gold is in great demand today, in an easy way and everyone can do it. Investment in the sale and purchase of old make the company very competitive. This study aims as a test of social media marketing, product innovation, celebrity endorser on purchasing decisions for jewelry at the Semar Nusantara gold shop Sukoharjo branch. The sample of this research is 100 consumers using the multiple linear regression method. Based on the results of research and discussion, social media marketing, product innovation, celebrity endorsers have a positive and significant effect on purchasing decisions at the Semar Nusantara gold shop. Social Media Marketing can influence purchasing decisions at the Semar Nusantara gold shop, Sukoharjo branch, which is one of the jewelry stores that keep up with the times, it can be said that because the jewelry shop offers online on social media, Instagram, and shopee in particular. So that millennials can buy online at the shopee @semarnusantara account and What's Up. With the social media Instagram @semarnusantara, customers can more easily find the latest information on the Semar Nusantara gold shop.